2012
DOI: 10.1038/nn.3142
|View full text |Cite
|
Sign up to set email alerts
|

miR-7a regulation of Pax6 controls spatial origin of forebrain dopaminergic neurons

Abstract: In the postnatal and adult mouse forebrain, a mosaic of spatially separated neural stem cells along the lateral wall of the ventricles generates defined types of olfactory bulb neurons. To understand the mechanisms underlying the regionalization of the stem cell pool, we focused on the transcription factor Pax6, a determinant of the dopaminergic phenotype in this system. We found that, although Pax6 mRNA was transcribed widely along the ventricular walls, Pax6 protein was restricted to the dorsal aspect. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 38 publications
11
124
0
2
Order By: Relevance
“…Viral transduction through this basal process targets NSCs in smaller V-SVZ areas, allowing investigators to describe postnatal V-SVZ regionalization in exquisite detail (Merkle et al, 2007(Merkle et al, , 2014. Results obtained by viral infection, genetic fatemapping or targeted electroporation experiments revealed that CR + PGCs are preferentially generated in the medial V-SVZ (Merkle et al, 2007(Merkle et al, , 2014Fernandez et al, 2011), whereas superficial GCs, tyrosine hydroxylase (TH)-expressing PGCs and a small number of glutamatergic juxtaglomerular cells are preferentially generated in the dorsal V-SVZ (Merkle et al, 2007;Young et al, 2007;Brill et al, 2009;Fernandez et al, 2011;de Chevigny et al, 2012), and deep GCs as well as CB + [expressing calbindin; also known as calbindin 1 (Calb1)] PGCs in the lateral aspect of the V-SVZ (Merkle et al, 2007;Young et al, 2007;Fernandez et al, 2011). A closer analysis of NSCs located in the most anterior ventral regions of the LV revealed the existence of additional microdomains.…”
Section: Embryonic Patterning Dictates V-svz Regionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral transduction through this basal process targets NSCs in smaller V-SVZ areas, allowing investigators to describe postnatal V-SVZ regionalization in exquisite detail (Merkle et al, 2007(Merkle et al, , 2014. Results obtained by viral infection, genetic fatemapping or targeted electroporation experiments revealed that CR + PGCs are preferentially generated in the medial V-SVZ (Merkle et al, 2007(Merkle et al, , 2014Fernandez et al, 2011), whereas superficial GCs, tyrosine hydroxylase (TH)-expressing PGCs and a small number of glutamatergic juxtaglomerular cells are preferentially generated in the dorsal V-SVZ (Merkle et al, 2007;Young et al, 2007;Brill et al, 2009;Fernandez et al, 2011;de Chevigny et al, 2012), and deep GCs as well as CB + [expressing calbindin; also known as calbindin 1 (Calb1)] PGCs in the lateral aspect of the V-SVZ (Merkle et al, 2007;Young et al, 2007;Fernandez et al, 2011). A closer analysis of NSCs located in the most anterior ventral regions of the LV revealed the existence of additional microdomains.…”
Section: Embryonic Patterning Dictates V-svz Regionalizationmentioning
confidence: 99%
“…The V-SVZ itself is therefore regionalized along the anteroposterior axis: rostrally located NSCs give rise to GCs that are more superficial in the GC layer than those generated by more caudally located NSCs (Kelsch et al, 2007). Furthermore, the V-SVZ is also patterned along the dorsoventral axis: selective electroporation of postnatal V-SVZ subregions (Fernandez et al, 2011;de Chevigny et al, 2012) showed that NSCs from the medial wall are biased to generate PGCs (>85%), whereas those from the lateral wall primarily adopt a GC fate (>90%). In an intermediate fashion, NSCs located in the dorsal wall generate PGCs and GCs in a 1 to 2 proportion (Fernandez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, electroporation can be tailored to the requirement of the respective experiment but not sweeping the electrode and using specific placement and orientation as detailed in the video. For example, since dorsally localized radial glia differ from those lining the lateral section of the ventricle, one can chose to only electroporate a single region 9,10 . Further specificity can also be given using smaller electrodes.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Close attention should be given to the placement given the heterogeneity of stem cell populations along the SVZ 8 . Differences in the rates of proliferation and cell fate have been identified for ventral-dorsal and rostral-caudal locations 9,10 .…”
mentioning
confidence: 99%
“…Nous avons montré qu'un microARN, miR-7a, limite la genèse de neurones dopaminergiques dans le bulbe olfactif post-natal en inhibant l'expression de la protéine Pax6 dans les précurseurs neuronaux des parois ventriculaires laté-rales [10]. Ce résultat nouveau ajoute un niveau de complexité à la régulation moléculaire de la destinée neuronale dans le cerveau adulte.…”
Section: Resultsunclassified